Self-lubricating PET (polyethylene terephthalate) resin composition as well as preparation method and application thereof
By adding PTFE, graphite and ceramic powder to the PET resin system, and adding elastomers and antioxidants, a lubricating PET resin composition was prepared, which solved the shortcomings of the PET resin material in terms of mechanical properties and friction coefficient, and achieved the self-lubricating, high flow and excellent mechanical properties of the material.
Patent Information
- Application Number
- CN202411600512.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-04-04
AI Technical Summary
Existing PET resin materials cannot meet the requirements of excellent mechanical properties and small friction coefficients in certain application fields.
By adding PTFE, graphite and ceramic powder to the PET resin system, the combination and synergistic combination of organic and inorganic lubricating materials was prepared to prepare a self-lubricating PET resin composition with a dynamic friction coefficient of less than 0.18 and a static friction coefficient of less than 0.20, and an elastomer and an antioxidant were added to balance the stiffness and strength of the material.
It realizes the self-lubricating, high flow and good molding functions of PET resin materials, and has excellent mechanical properties and low friction coefficient. It is suitable for cosmetic packaging containers, household electronics and office supplies and other fields.
Smart Images

Figure BDA0005128178850000111 
Figure BDA0005128178850000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a self-lubricating PET resin composition and a preparation method and application thereof. Background Art
[0002] Polyethylene terephthalate (PET), commonly known as polyester resin, is obtained by ester exchange of dimethyl terephthalate with ethylene glycol or esterification of terephthalic acid with ethylene glycol to synthesize dihydroxyethyl terephthalate, and then polycondensation reaction. PET resin is the most important variety of thermoplastic polyester. It is a milky white or light yellow, highly crystalline polymer with a smooth and shiny surface. It has the advantages of high heat resistance, high toughness, high fatigue resistance, self-lubrication, and friction resistance. It is widely used in packaging materials, textiles and clothing, automobiles, home appliances and other industries. Although PET resin itself has the advantage of a low friction coefficient, in some specific fields, its mechanical strength and friction performance still cannot meet the product use requirements.
[0003] In the prior art, the patent with application number 201910486971.4 discloses an additive and a preparation method, a PP / PET blended modified material and a preparation method. The additive is a silicone rubber powder elastomer formed by accelerating vulcanization of vinyl silicone oil and hydrogen-containing silicone oil in hot water under the action of an emulsifier and a catalyst. It is applied as a lubricant in the PP / PET blending modification process. The prepared PP / PET blended material has a small friction coefficient, good wear resistance, and the preparation process is easy to control. In this patent, the resin matrix is lubricated at the molecular scale by the additive, thereby achieving the purpose of reducing the friction coefficient, but the mechanical property modification effect of the resin matrix is general, and the final PP / PET blended modified material cannot have both excellent mechanical properties and a small friction coefficient.
[0004] The patent with application number 201811546878.X discloses a self-lubricating PET fiber composite material and its preparation method, which is made by mixing polyethylene terephthalate materials, polybutylene terephthalate materials, cationic modified copolyether esters, etc. in a specific proportion. Using polyethylene terephthalate materials as the main material can achieve cost control on the one hand, and maintain the good mechanical properties and aging resistance of the composite material on the other hand. Polybutylene terephthalate materials have the characteristics of low friction coefficient, self-lubrication, low water absorption, and excellent chemical resistance, which is conducive to improving the self-lubrication of the composite material. The addition of cationic modified copolyether ester can not only effectively improve the color absorption rate and improve the dyeing performance, but also has good softness, overcoming the shortcomings of polyethylene terephthalate materials that are easy to pill, hygroscopic and antistatic. In this patent, through the compounding of multiple resin materials, the final composite material has good mechanical properties and aging resistance, and also has certain self-lubricating properties. The zipper of the product made of the above composite material has no noise during testing, but the improvement effect of the friction performance of the material is still not obvious, and the requirement of a friction coefficient of less than 0.2 cannot be met. Summary of the invention
[0005] In order to solve the problems existing in the above background technology, the present invention provides a self-lubricating PET resin composition, by adding PTFE (polytetrafluoroethylene), graphite, and ceramic powder to the PET resin system, the organic lubricating material and the inorganic lubricating material are compounded and synergistically combined, and a PET resin composition with a friction coefficient of less than 0.2, self-lubricating, high flow, and good molding functions is obtained. At the same time, other auxiliary agents such as elastomers and antioxidants are added to the product system to achieve a balance between the stiffness and strength of the material properties. In addition, the present invention also provides a preparation method of the above self-lubricating PET resin composition and uses it in the fields of cosmetic packaging containers, household electronics, office supplies, etc.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The first aspect of the present invention provides a self-lubricating PET resin composition, comprising the following raw material components in parts by weight:
[0008] PET resin 50-95 parts;
[0009] 1-10 parts of polytetrafluoroethylene;
[0010] Graphite 0.1-5 parts;
[0011] 0.1 to 5 parts of ceramic powder;
[0012] 0.1 to 5 parts of inorganic filler;
[0013] Elastomer 0-10 parts;
[0014] Titanium dioxide 0-5 parts;
[0015] Antioxidant 0-1 part.
[0016] Further, the raw material components include the following parts by weight:
[0017] PET resin 70-95 parts;
[0018] 2-7 parts of polytetrafluoroethylene;
[0019] 1-5 parts of graphite;
[0020] 1 to 5 parts of ceramic powder;
[0021] 0.5-3 parts of inorganic filler;
[0022] 1 to 5 parts of elastomer;
[0023] 1 to 5 parts of titanium dioxide;
[0024] Antioxidant 0.1 to 1 part.
[0025] Furthermore, the ceramic powder is boron nitride or silicon nitride.
[0026] Preferably, the ceramic powder is boron nitride.
[0027] Preferably, the average particle size of the boron nitride is 20 to 80 μm.
[0028] Through experiments and verification, it is found that when different types of ceramic powders are added to the product system, and the ceramic powder is boron nitride or silicon nitride, the self-lubricating PET resin products obtained have the best mechanical properties and a lower friction coefficient.
[0029] When boron nitride is used as ceramic powder, the self-lubricating PET resin product has a lower friction coefficient than silicon nitride. By testing boron nitride with different particle sizes, it is finally found that when the average particle size of boron nitride is controlled within the range of 20 to 80 μm, the mechanical properties of the self-lubricating PET resin product are better, and it has a lower dynamic friction coefficient and static friction coefficient.
[0030] Furthermore, the antioxidant is a mixture of antioxidant 1010 and antioxidant 168.
[0031] Furthermore, the inorganic filler is calcium carbonate, talcum powder, mica powder, quartz powder, etc.
[0032] The elastomer may be styrene elastomer TPS, olefin elastomer TPO, polyurethane elastomer TPU, polyester elastomer TPEE, etc.
[0033] The second aspect of the present invention provides a method for preparing the self-lubricating PET resin composition, comprising the following steps:
[0034] S1, adding each raw material component into a high-speed mixer in sequence and mixing them evenly to obtain a mixed material;
[0035] S2, adding the mixed material into a twin-screw extruder, and performing melt blending and extrusion granulation to obtain a self-lubricating PET resin composition material.
[0036] Furthermore, in step S2, the melting temperature is 180-280° C., and the screw speed is 200-600 rpm.
[0037] Preferably, in step S2, the melting temperature is 240-270°C, and the screw speed is 300-500 rpm.
[0038] The third aspect of the present invention provides an application of the above-mentioned self-lubricating PET resin composition, wherein the self-lubricating PET resin composition is molded at 180-280°C to obtain a self-lubricating PET composite material product, and the self-lubricating PET composite material product is used in cosmetic packaging containers (such as cosmetic packaging bottle caps), household electronics or office supplies.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] (1) In the present invention, PTFE, graphite, and ceramic powder are added to the PET resin system as lubricating materials, and the organic lubricating materials and inorganic lubricating materials are compounded and synergistically combined to obtain a PET resin composition with a dynamic friction coefficient of less than 0.18 and a static friction coefficient of less than 0.20, which has self-lubricating, high flowability, and good molding functions. The lubrication principle of graphite is to reduce the friction coefficient by causing the interface friction slip of the material; the lubrication principle of PTFE is to reduce the friction coefficient by lubricating the material at the molecular scale; after adding these two materials (PTFE and graphite) to the product system, heat is generated during the friction process, causing the interface of the material to be destroyed, which plays the opposite role of increasing wear. In the present invention, ceramic powder is selected to be added to the product system and compounded with PTFE and graphite. The ceramic powder effectively removes the friction heat when the material generates heat by friction, maintains the interface stiffness and smoothness, thereby reducing wear. At the same time, the ceramic powder itself also has the characteristic of low friction coefficient.
[0041] (2) In the present invention, other additives, such as elastomers and antioxidants, are added to the product system to achieve a balance between the stiffness and strength of the material properties. The self-lubricating PET resin composition obtained has excellent mechanical properties and low dynamic and static friction coefficients.
[0042] (3) The self-lubricating PET resin composition of the present invention can be used in the fields of cosmetic packaging containers, household electronics, office supplies, etc., and in particular, can be used in cosmetic packaging bottle caps. The cosmetic packaging bottle caps have less friction when being opened or tightened from the bottle body, and the user experience is better. DETAILED DESCRIPTION
[0043] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Example 1
[0045] The self-lubricating PET resin composition in this embodiment includes the following raw material components in parts by weight:
[0046] PET resin 82 parts;
[0047] 5 parts of polytetrafluoroethylene;
[0048] 2 parts of graphite;
[0049] 1 part of ceramic powder;
[0050] 1 part of inorganic filler;
[0051] 1.5 parts of elastomer;
[0052] 1.5 parts of titanium dioxide;
[0053] 0.6 parts of antioxidant.
[0054] The ceramic powder is boron nitride with an average particle size of 100 μm, the inorganic filler is calcium carbonate, the elastomer is olefin elastomer TPO, and the antioxidant is antioxidant 1010 and antioxidant 168 with a mass ratio of 1:1.
[0055] The preparation method of the self-lubricating PET resin composition in this embodiment is as follows:
[0056] S1. Add each raw material component into a high-speed mixer in sequence, stir at a low speed of 50 rpm for 2 minutes, and stir at a high speed of 200 rpm for 5 minutes to obtain a mixed material;
[0057] S2, adding the mixed material into a twin-screw extruder, and performing melt blending and extrusion granulation to obtain a self-lubricating PET resin composition material.
[0058] Furthermore, in step S2, the melting temperature is 260° C. and the screw speed is 400 rpm.
[0059] Example 2
[0060] The self-lubricating PET resin composition in this embodiment includes the following raw material components in parts by weight:
[0061] PET resin 82 parts;
[0062] 5 parts of polytetrafluoroethylene;
[0063] 2 parts of graphite;
[0064] 1 part of ceramic powder;
[0065] 1 part of inorganic filler;
[0066] 1.5 parts of elastomer;
[0067] 1.5 parts of titanium dioxide;
[0068] 0.6 parts of antioxidant.
[0069] The ceramic powder is boron nitride with an average particle size of 30 μm, the inorganic filler is calcium carbonate, the elastomer is olefin elastomer TPO, and the antioxidants are antioxidant 1010 and antioxidant 168 with a mass ratio of 1:1.
[0070] The preparation method of the self-lubricating PET resin composition in this embodiment is the same as that in Example 1.
[0071] Example 3
[0072] The self-lubricating PET resin composition in this embodiment includes the following raw material components in parts by weight:
[0073] PET resin 82 parts;
[0074] 5 parts of polytetrafluoroethylene;
[0075] 2 parts of graphite;
[0076] 1 part of ceramic powder;
[0077] 1 part of inorganic filler;
[0078] 1.5 parts of elastomer;
[0079] 1.5 parts of titanium dioxide;
[0080] 0.6 parts of antioxidant.
[0081] The ceramic powder is boron nitride with an average particle size of 5 μm, the inorganic filler is calcium carbonate, the elastomer is olefin elastomer TPO, and the antioxidants are antioxidant 1010 and antioxidant 168 with a mass ratio of 1:1.
[0082] The preparation method of the self-lubricating PET resin composition in this embodiment is the same as that in Example 1.
[0083] Example 4
[0084] The self-lubricating PET resin composition in this embodiment includes the following raw material components in parts by weight:
[0085] PET resin 82 parts;
[0086] 5 parts of polytetrafluoroethylene;
[0087] 2 parts of graphite;
[0088] 1 part of ceramic powder;
[0089] 1 part of inorganic filler;
[0090] 1.5 parts of elastomer;
[0091] 1.5 parts of titanium dioxide;
[0092] 0.6 parts of antioxidant.
[0093] The ceramic powder is silicon nitride, the inorganic filler is calcium carbonate, the elastomer is olefin elastomer TPO, and the antioxidants are antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1.
[0094] The preparation method of the self-lubricating PET resin composition in this embodiment is the same as that in Example 1.
[0095] Example 5
[0096] The self-lubricating PET resin composition in this embodiment includes the following raw material components in parts by weight:
[0097] PET resin 82 parts;
[0098] 5 parts of polytetrafluoroethylene;
[0099] 2 parts of graphite;
[0100] 3 parts of ceramic powder;
[0101] 1 part of inorganic filler;
[0102] 1.5 parts of elastomer;
[0103] 1.5 parts of titanium dioxide;
[0104] 0.6 parts of antioxidant.
[0105] The ceramic powder is boron nitride with an average particle size of 30 μm, the inorganic filler is calcium carbonate, the elastomer is olefin elastomer TPO, and the antioxidants are antioxidant 1010 and antioxidant 168 with a mass ratio of 1:1.
[0106] The preparation method of the self-lubricating PET resin composition in this embodiment is the same as that in Example 1.
[0107] Example 6
[0108] The self-lubricating PET resin composition in this embodiment includes the following raw material components in parts by weight:
[0109] PET resin 82 parts;
[0110] 5 parts of polytetrafluoroethylene;
[0111] 2 parts of graphite;
[0112] 5 parts of ceramic powder;
[0113] 1 part of inorganic filler;
[0114] 1.5 parts of elastomer;
[0115] 1.5 parts of titanium dioxide;
[0116] 0.6 parts of antioxidant.
[0117] The ceramic powder is boron nitride with an average particle size of 30 μm, the inorganic filler is calcium carbonate, the elastomer is olefin elastomer TPO, and the antioxidants are antioxidant 1010 and antioxidant 168 with a mass ratio of 1:1.
[0118] The preparation method of the self-lubricating PET resin composition in this embodiment is the same as that in Example 1.
[0119] Comparative Example 1
[0120] The self-lubricating PET resin composition in this embodiment includes the following raw material components in parts by weight:
[0121] PET resin 82 parts;
[0122] 5 parts of polytetrafluoroethylene;
[0123] 2 parts of graphite;
[0124] 7 parts of ceramic powder;
[0125] 1 part of inorganic filler;
[0126] 1.5 parts of elastomer;
[0127] 1.5 parts of titanium dioxide;
[0128] 0.6 parts of antioxidant.
[0129] The ceramic powder is boron nitride with an average particle size of 30 μm, the inorganic filler is calcium carbonate, the elastomer is olefin elastomer TPO, and the antioxidants are antioxidant 1010 and antioxidant 168 with a mass ratio of 1:1.
[0130] The preparation method of the self-lubricating PET resin composition in this comparative example is the same as that in Example 1.
[0131] Comparative Example 2
[0132] The self-lubricating PET resin composition in this embodiment includes the following raw material components in parts by weight:
[0133] PET resin 82 parts;
[0134] 5 parts of polytetrafluoroethylene;
[0135] 2 parts of graphite;
[0136] 1 part of inorganic filler;
[0137] 1.5 parts of elastomer;
[0138] 1.5 parts of titanium dioxide;
[0139] 0.6 parts of antioxidant.
[0140] The inorganic filler is calcium carbonate, the elastomer is olefin elastomer TPO, and the antioxidants are antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1.
[0141] The preparation method of the self-lubricating PET resin composition in this comparative example is the same as that in Example 1.
[0142] Comparative Example 3
[0143] The self-lubricating PET resin composition in this embodiment includes the following raw material components in parts by weight:
[0144] PET resin 82 parts;
[0145] 5 parts of polytetrafluoroethylene;
[0146] 1 part of ceramic powder;
[0147] 1 part of inorganic filler;
[0148] 1.5 parts of elastomer;
[0149] 1.5 parts of titanium dioxide;
[0150] 0.6 parts of antioxidant.
[0151] The ceramic powder is boron nitride with an average particle size of 30 μm, the inorganic filler is calcium carbonate, the elastomer is olefin elastomer TPO, and the antioxidants are antioxidant 1010 and antioxidant 168 with a mass ratio of 1:1.
[0152] The preparation method of the self-lubricating PET resin composition in this comparative example is the same as that in Example 1.
[0153] Comparative Example 4
[0154] The self-lubricating PET resin composition in this embodiment includes the following raw material components in parts by weight:
[0155] PET resin 82 parts;
[0156] 2 parts of graphite;
[0157] 1 part of ceramic powder;
[0158] 1 part of inorganic filler;
[0159] 1.5 parts of elastomer;
[0160] 1.5 parts of titanium dioxide;
[0161] 0.6 parts of antioxidant.
[0162] The ceramic powder is boron nitride with an average particle size of 30 μm, the inorganic filler is calcium carbonate, the elastomer is olefin elastomer TPO, and the antioxidants are antioxidant 1010 and antioxidant 168 with a mass ratio of 1:1.
[0163] The preparation method of the self-lubricating PET resin composition in this comparative example is the same as that in Example 1.
[0164] Comparative Example 5
[0165] The self-lubricating PET resin composition in this embodiment includes the following raw material components in parts by weight:
[0166] PET resin 82 parts;
[0167] 1 part of ceramic powder;
[0168] 1 part of inorganic filler;
[0169] 1.5 parts of elastomer;
[0170] 1.5 parts of titanium dioxide;
[0171] 0.6 parts of antioxidant.
[0172] The ceramic powder is boron nitride with an average particle size of 30 μm, the inorganic filler is calcium carbonate, the elastomer is olefin elastomer TPO, and the antioxidants are antioxidant 1010 and antioxidant 168 with a mass ratio of 1:1.
[0173] The preparation method of the self-lubricating PET resin composition in this comparative example is the same as that in Example 1.
[0174] Example 7
[0175] The self-lubricating PET resin composition in this embodiment includes the following raw material components in parts by weight:
[0176] PET resin 50 parts;
[0177] 1 part of polytetrafluoroethylene;
[0178] 0.1 part of graphite;
[0179] 0.1 part of ceramic powder;
[0180] 0.1 part of inorganic filler;
[0181] Elastomer 0.1 part;
[0182] 0.1 part of titanium dioxide;
[0183] Antioxidant 0.1 part.
[0184] The ceramic powder is boron nitride with an average particle size of 30 μm, the inorganic filler is calcium carbonate, the elastomer is olefin elastomer TPO, and the antioxidants are antioxidant 1010 and antioxidant 168 with a mass ratio of 1:1.
[0185] The preparation method of the self-lubricating PET resin composition in this embodiment is as follows:
[0186] S1. Add each raw material component into a high-speed mixer in sequence, stir at a low speed of 50 rpm for 2 minutes, and stir at a high speed of 200 rpm for 5 minutes to obtain a mixed material;
[0187] S2, adding the mixed material into a twin-screw extruder, and performing melt blending and extrusion granulation to obtain a self-lubricating PET resin composition material.
[0188] Furthermore, in step S2, the melting temperature is 240° C. and the screw speed is 300 rpm.
[0189] Example 8
[0190] The self-lubricating PET resin composition in this embodiment includes the following raw material components in parts by weight:
[0191] PET resin 70 parts;
[0192] 2 parts of polytetrafluoroethylene;
[0193] 1 part of graphite;
[0194] 1 part of ceramic powder;
[0195] 0.5 parts of inorganic filler;
[0196] 1 part of elastomer;
[0197] 1 part of titanium dioxide;
[0198] 0.6 parts of antioxidant.
[0199] The ceramic powder is boron nitride with an average particle size of 30 μm, the inorganic filler is calcium carbonate, the elastomer is olefin elastomer TPO, and the antioxidants are antioxidant 1010 and antioxidant 168 with a mass ratio of 1:1.
[0200] The preparation method of the self-lubricating PET resin composition in this embodiment is as follows:
[0201] S1. Add each raw material component into a high-speed mixer in sequence, stir at a low speed of 50 rpm for 2 minutes, and stir at a high speed of 200 rpm for 5 minutes to obtain a mixed material;
[0202] S2, adding the mixed material into a twin-screw extruder, and performing melt blending and extrusion granulation to obtain a self-lubricating PET resin composition material.
[0203] Furthermore, in step S2, the melting temperature is 270° C. and the screw speed is 500 rpm.
[0204] Example 9
[0205] The self-lubricating PET resin composition in this embodiment includes the following raw material components in parts by weight:
[0206] PET resin 95 parts;
[0207] 7 parts of polytetrafluoroethylene;
[0208] Graphite 5 parts;
[0209] 5 parts of ceramic powder;
[0210] 3 parts of inorganic filler;
[0211] 5 parts of elastomer;
[0212] 5 parts of titanium dioxide;
[0213] 1 part antioxidant.
[0214] The ceramic powder is boron nitride with an average particle size of 30 μm, the inorganic filler is calcium carbonate, the elastomer is olefin elastomer TPO, and the antioxidants are antioxidant 1010 and antioxidant 168 with a mass ratio of 1:1.
[0215] The preparation method of the self-lubricating PET resin composition in this embodiment is as follows:
[0216] S1. Add each raw material component into a high-speed mixer in sequence, stir at a low speed of 50 rpm for 2 minutes, and stir at a high speed of 200 rpm for 5 minutes to obtain a mixed material;
[0217] S2, adding the mixed material into a twin-screw extruder, and performing melt blending and extrusion granulation to obtain a self-lubricating PET resin composition material.
[0218] Furthermore, in step S2, the melting temperature is 280° C. and the screw speed is 600 rpm.
[0219] Example 10
[0220] The self-lubricating PET resin composition in this embodiment includes the following raw material components in parts by weight:
[0221] PET resin 90 parts;
[0222] 10 parts of polytetrafluoroethylene;
[0223] 4 parts of graphite;
[0224] 3 parts of ceramic powder;
[0225] 5 parts of inorganic filler;
[0226] Elastomer 10 parts;
[0227] 2 parts of titanium dioxide;
[0228] 0.6 parts of antioxidant.
[0229] The ceramic powder is boron nitride with an average particle size of 30 μm, the inorganic filler is calcium carbonate, the elastomer is olefin elastomer TPO, and the antioxidants are antioxidant 1010 and antioxidant 168 with a mass ratio of 1:1.
[0230] The preparation method of the self-lubricating PET resin composition in this embodiment is as follows:
[0231] S1. Add each raw material component into a high-speed mixer in sequence, stir at a low speed of 50 rpm for 2 minutes, and stir at a high speed of 200 rpm for 5 minutes to obtain a mixed material;
[0232] S2, adding the mixed material into a twin-screw extruder, and performing melt blending and extrusion granulation to obtain a self-lubricating PET resin composition material.
[0233] Furthermore, in step S2, the melting temperature is 180° C. and the screw speed is 200 rpm.
[0234] The self-lubricating PET resin compositions prepared in Examples 1 to 10 and Comparative Examples 1 to 5 were molded at 180 to 280° C. to obtain self-lubricating PET composite products, and their properties were tested. The test results are shown in Table 1.
[0235] Flexural strength is tested according to ISO 527, flexural modulus is tested according to ISO 178, tensile strength is tested according to ISO 178, and impact strength (unnotched) is tested according to ISO 180.
[0236] The melt index is tested according to ISO 1133 standard and the product density is tested according to ISO 1183 standard.
[0237] The dynamic friction coefficient and static friction coefficient are tested in accordance with GB / T 10006-2021.
[0238] The method for testing the torque for opening the cap is as follows: the self-lubricating PET resin compositions prepared in Examples 1 to 10 and Comparative Examples 1 to 5 are respectively made into cosmetic packaging bottle caps, the cosmetic packaging can body is made of PETG (polyethylene terephthalate-1,4-cyclohexanedimethanol ester), and after the bottle cap is tightened on the can body, a torque test for unscrewing the bottle cap is performed.
[0239] Table 1
[0240]
[0241]
[0242] It can be seen from the test results in Table 1 that by comparing Examples 1 to 4, different types and different particle sizes of ceramic powders are used in the product systems, respectively. In Example 1, boron nitride with an average particle size of 100 μm is used as the ceramic powder, in Example 2, boron nitride with an average particle size of 30 μm is used as the ceramic powder, in Example 3, boron nitride with an average particle size of 5 μm is used as the ceramic powder, and in Example 4, silicon nitride is used as the ceramic powder. After experimental testing, the overall performance of the products obtained in Examples 1 to 3 is better than that in Example 4, among which the product obtained in Example 2 has the best mechanical properties, and the dynamic and static friction coefficients and the smallest cover opening torque, indicating that the overall performance of the product obtained when boron nitride is used as the ceramic powder is better than the overall performance of the product obtained when silicon nitride is used as the ceramic powder, and the average particle size of aluminum nitride is preferably 20 to 80 μm.
[0243] Comparing Examples 1, 5, 6 and Comparative Example 1, the difference among the four is that the amount of ceramic powder in the system is different. The amount of ceramic powder in Example 1 is 1 weight part, the amount of ceramic powder in Example 5 is 3 weight parts, the amount of ceramic powder in Example 6 is 5 weight parts, and the amount of ceramic powder in Comparative Example 1 is 7 weight parts. The product performance is tested. The overall performance of the product prepared in Example 5 is the best (especially the dynamic friction coefficient and the static friction coefficient are both less than 0.15, and the cover opening torque is 8.5 Kgf.cm), and the overall performance of the product prepared in Comparative Example 1 is the worst, indicating that the amount of ceramic powder in the product system of the present invention is preferably 1 to 5 weight parts, and more preferably 3 weight parts.
[0244] Comparing Example 2 with Comparative Examples 2 to 5, the difference between them is that PTFE, graphite and ceramic powder (boron nitride with an average particle size of 30 μm) are compounded in the product system of Example 2, PTFE and graphite are compounded in the product system of Comparative Example 2, and ceramic powder is not added, PTFE and ceramic powder (boron nitride with an average particle size of 30 μm) are compounded in the product system of Comparative Example 3, and graphite is not added, and PTFE is not added in the product system of Comparative Example 4, and ceramic powder (boron nitride with an average particle size of 30 μm) is compounded in the product system of Comparative Example 5, and PTFE and graphite are not added. The product performance is tested, and the mechanical properties of the product of Example 2 are better than those of Comparative Examples 2 to 5, and the dynamic friction coefficient, static friction coefficient and cover opening torque of the product of Example 2 are significantly lower than those of the products prepared in Comparative Examples 2 to 5, indicating that PTFE, graphite and ceramic powder in the product system of the present invention play a synergistic role.
[0245] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A self-lubricating PET resin composition, characterized in that: The raw material components include the following parts by weight: PET resin 50-95 parts; 1-10 parts of polytetrafluoroethylene; Graphite 0.1-5 parts; 0.1 to 5 parts of ceramic powder; 0.1 to 5 parts of inorganic filler; Elastomer 0-10 parts; Titanium dioxide 0-5 parts; Antioxidant 0-1 part.
2. The self-lubricating PET resin composition according to claim 1, characterized in that: The raw material components include the following parts by weight: PET resin 70-95 parts; 2-7 parts of polytetrafluoroethylene; 1-5 parts of graphite; 1 to 5 parts of ceramic powder; 0.5-3 parts of inorganic filler; 1 to 5 parts of elastomer; 1 to 5 parts of titanium dioxide; Antioxidant 0.1 to 1 part.
3. The self-lubricating PET resin composition according to claim 1 or 2, characterized in that: The ceramic powder is boron nitride or silicon nitride.
4. The self-lubricating PET resin composition according to claim 3, characterized in that: The ceramic powder is boron nitride.
5. The self-lubricating PET resin composition according to claim 4, characterized in that: The average particle size of the boron nitride is 20 to 80 μm.
6. The self-lubricating PET resin composition according to claim 1, characterized in that: The antioxidant is a mixture of antioxidant 1010 and antioxidant 168.
7. The self-lubricating PET resin composition according to claim 1, characterized in that: The inorganic filler is calcium carbonate, talcum powder, mica powder or quartz powder.
8. A method for preparing a self-lubricating PET resin composition as claimed in any one of claims 1 to 7, characterized in that: The steps include: S1, adding each raw material component into a high-speed mixer in sequence and mixing them evenly to obtain a mixed material; S2, adding the mixed material into a twin-screw extruder, and performing melt blending and extrusion granulation to obtain a self-lubricating PET resin composition material.
9. The method for preparing the self-lubricating PET resin composition according to claim 8, characterized in that: In the step S2, the melting temperature is 180-280°C, and the screw speed is 200-600 rpm.
10. An application of the self-lubricating PET resin composition according to any one of claims 1 to 7, characterized in that: The self-lubricating PET resin composition is molded at 180-280° C. to obtain a self-lubricating PET composite material product, which is used in the fields of cosmetic packaging containers, household electronics or office supplies.
Citation Information
Patent Citations
A self-lubricating PET fiber composite material and its preparation method
CN109575535B
Additive and its preparation method, PP / PET blending modified material and its preparation method
CN110093040A
Wear-resistant filling material, wear-resistant composite material prepared from same and preparation method for composite material
CN103788403A
High-wear-resistance self-lubrication polyethylene terephthalate and preparation method thereof
CN104788917A